1)х=53
2)у=22
3)у=14
4)у=303
17
х²+2х-3=0
D=4+12=16
x1=-2+4 / 2 = 1
x2=-2-4 / 2=-3
18
x²+2x-4=0
D=4+16=20
x1=-2-2√5 / 2 = -1-√5
x2=-2+2√5 / 2 = √5-1
19
x²-5x-6=0
D=25+24=49
x1=5+7 / 2=6
x2 = 5-7 / 2 = -1
20
2x²-2x-4=0
x²-x-2=0
D=1+8=9
x1=1+3 / 2=2
x2 = 1-3 / 2 = -1
30
одз х≠0
4х-х²=0
х(4-х)=0
х=0 - не входит в одз
х=4
ответ х=4
29
одз х≠0
4-х²=0
х²=4
х1=2
х2=-2
Х²-4*у=4 4*у=х²-4 у=(х²/4)-1
х-у=1 у=х-1
у=у (х²/4)-1=х-1 (х²/4)-х=0 х²-4*х=0 х*(х-4)=0 х=0 х-4=0 х=4
х=0 у=0-1=-1 (0; -1)
х=4 у=4-1=3 (4; 3)
<span>A-M/A-B=C-D/C-E
( А - М )( С - Е ) = ( А - В )( С - D )
A - M = (( A - B )( C - D )) / ( C - E )
M = A - </span><span>(( A - B )( C - D )) / ( C - E )
M = ( A( C - E ) - ( A - B )( C - D )) / ( C - E )
M = ( AC - AE - ( AC - AD - BC + CD ) / ( C - E )
M = ( AC - AE - AC + AD + BC - CD ) / ( C - E )
M = ( AD + BC - AE - CD ) / ( C - E ) </span>